Lectotypification of Fimbristylis tenera (Cyperaceae) - Halder, Suman; Kumar, Anant; Dey, Sangita; Venu, Potharaju (Phytotaxa, 2014)
A lectotype is designated for Fimbristylis tenera Roem. & Schult. to fix the current usage of the name.